Etika Bisnis dan Perilaku Etis Manajer Pengaruhnya terhadap Tanggung Jawab Perusahaan pada Lingkungan Sosial - Andjarwati, Anik Lestari; Budiadi, Setijo (BISMA (Bisnis dan Manajemen), 2018)
The purpose of this research is examine the manager busines ethics to manager ethical behavior, examining manager business ethics to corporate social responsibility; and examine the effect of manager ethical behavior to corporate social responsibility. To select the respondent researcher was used purposive sampling, the analysis technique uses is Structural Equation Modeling (SEM). The research behavior show that; (1) business ethics positevely effects to manager ethical behavior; (2) Manager ethical behavior positively affect to corporate social responsibility; (3) Business ethics positively affects to corparate social responsibility.